Suicide squad [videorecording (Blu-Ray)] - Ayer, David; Smith, Will, 1968-; Leto, Jared, 1971-; Robbie, Margot, 1990-; Kinnaman, Joel, 1979-; Davis, Viola, 1965-; Courtney, Jai; Hernandez, Jay, 1978-; Akinnuoye-Agbaje, Adewale, 1967-; Delevingne, Cara, 1992-; Barinholtz, Ike, 1977-; Eastwood, Scott, 1986-; et al. (Warner Bros. Home Entertainment, 2016)
U.S. intelligence officer Amanda Waller has determined that only a secret group of despicable individuals with nothing to lose can avert a potential apocalypse. So, she has assembled the world's most dangerous super villains, given them a powerful arsenal of weapons, and sent them off on a suicide mission.